The Correlation of ultrasonic wave characteristics with pull out strength as the corrosion in reinforced concrete progresses with time - Caram, Rosabelle Louise A.
Corrosion brings about a decrease in the strength of the rebar and the bond strength of the concrete surrounding it, as well as a reduction in the cross-section of the rebar. At present, people are finding ways to mitigate the problem however, this approach will only postpone the collapse of a structure for a certain period of time. Therefore it is important to find a non-destructive way of classifying and checking the behaviour of a structure at any given time. As the popularity of high-rise structures increases, so does the total number of future structures that will need to be retrofitted and checked for serviceability, this explains why the study is limited to design strengths for high-rise buildings. This study aims to correlate the Ultrasonic wave characteristics of reinforced concrete with its puLl out strength as it is corroded. All specimens were of the same size, same design concrete strength and rebar size and were subject to a highly corrosive environment produced with 10% NaCl and electrolytic corrosion. The accelerated corrosion was done over a maximum period of 115 days before specimens were subjected to Ultrasonic tests as well as pull-out tests, to map out the corrosion of the rebar and the strength that it offers. Statistical analysis showed that significant relationship was. Possible sources of error may have come from some irregularities in the surfaces of the specimens, as well as from the DC power supply's inability to yield more than 3A of current for the accelerated corrosion set-up.